Interaction of nuclear radiations with scintillation crystals ZnSe(O, Te) - Gal’chinetskii, L.P.; Ryzhikov, V.D.; Starzhinskiy, N.G. (Вопросы атомной науки и техники, 2006)
The experimental data on the irradiation of ZnSe(О,Те)-crystals with γ-quanta, protons and neutrons are presented and discussed. The mechanism for heightening the concentration of luminescence centers of C1-type ZniVZnТеSe (λmax≈640 nm) and C2-type VZnZniОSe (λmax≈605 nm), accompanied by an increase in the radioluminescence intensity, is submitted. During p-irradiation, hydrogen, generated in the process of proton thermalization, interacts with oxygen that the C2-centers contain, which results in the C2-center destruction, a decrease in the intensity and the λ max shift towards the long-wave range. Приведены результаты экспериментов по облучению кристаллов ZnSe(О,Те) γ-квантами, протонами, нейтронами. Предложен механизм увеличения при n-облучении концентрации центров люминесценции Ц1 типа ZniVZnТеSe (λmax≈640 нм) и Ц2 типа VZnZniОSe (λmax≈605 нм), сопровождающий возрастанием интенсивности I радиолюминесценции (РЛ). При p-облучении водород, образующийся в процессе термализации протонов, взаимодействует с кислородом, входящим в состав Ц2; это приводит к разрушению Ц2, уменьшению I РЛ и к длинноволновому сдвигу λmax. Наведено результати експериментів з опромінення кристалів ZnSe(О,Те) γ-квантами, протонами, нейтро- нами. Запропоновано механізм збільшення під час n-опромінення концентрації центрів люмінесценції Ц1 типу ZniVZnТеSe (λmax≈640 нм) та Ц2 типу VZnZniОSe (λmax≈605 нм), якиї супроводжується зростанням інтенсивності I радіолюмінесценції (РЛ). Під час p-опромінення водень, що утворюється в процесі термалізації протонів, взаємодіє з киснем, який входить до складу Ц2; це призводить до зруйнування Ц2, зменшення I РЛ та до довгохвильового зсуву λmax.